GUIDELINES FOR THE DIAGNOSIS AND MANAGEMENT OF SYNCOPE (2009) - Angel Moya; Richard Sutton; Fabrizio Ammirati; Jean-Jacques Blanc; Michele Brignole; Johannes B. Dahm; Jean-Claude Deharo; Jacek Gajek; Knut Gjesdal; Andrew Krahn; Martial Massin; Mauro Pepi; et al. (Столичная издательская компания, 2016)
Guidelines for the diagnosis and management of syncope (2009).